On equivariant extensions of a differential operator by the example of the Laplace operator in a circle - Burskii, V. P. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We propose a method for investigation of both correctness of the equivariant problem and the spectrum of the corresponding operator.